Critical success factors for market strategy in electric vehicles - Pedro Marques; Pereira, L.; Santos, J.; Lopes da Costa, R.; Dias, Á. (International Journal of Business Innovation and Research, 2021)
The increasing consuming levels of fossil fuels are contributing dramatically and significantly to the climate change. Based on this assumption the automotive industry has decided to contribute to a sustainable initiative by investing in battery electric vehicle (BEV) fleets and new all purpose vehicle (APV) options, which have the purpose of enhancing and facilitate the mobility inside cities. This paper aims to estimate the impact and changes in the Portuguese transportation sector, as well to assess the customer perception and identify the decision-making factors of an electric vehicle. The results predict a growth of the APV in Europe and in Portugal along with average age of the Portuguese automotive car park. It is also expected a growth of the charging points infrastructure and the mobility options within the city. Moreover, the price and autonomy are the two most valued factors in an EV and the brand and technology the least.